PROGRES KEMAJUAN KOMUNITAS MISKIN DI PERKOTAAN : URGENSI KEIKUTSERTAAN MASYARAKAT - Nata, Andrian Anwar L (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
This article attempts to contribute to practical considerations of community participation in development activities in poor urban communities. Therefore, comprehensive intervention is needed and involves various stakeholders from the authorities as well as various stakeholders such as volunteer organizations, companies, universities and the community. Action research is applied research that uses knowledge as a form of power and eliminates the boundaries between research and social action. Assistance to the poor is an effort to alleviate poverty because the recipient had a business before receiving assistance and did not meet the average criteria for assistance. This is a job that does not take into account the professionalism of the work. For the urban poor community empowerment model, there are 4 development stages, namely the potential development stage, the social accumulation stage (employment potential), the social participation stage and the special stage. Community action as a local force can create a model of community empowerment that relies on the principles of ecology and social justice and upholds human rights values. The idea is that implementing a model of strengthening local poor communities in urban areas can change the nature of the social development model, rather than developing society from the economic sector, but must be accompanied by an understanding of the potential of the community, the potential and potential that the community has, the greater their hopes and building a better society.